Pengembangan Panduan Achievement Motivation Training untuk Meningkatkan Efikasi Diri Akademik Siswa SMP - Hidayatul Isnaeni; Asrowi Asrowi; Ribut Purwaningrum (Jurnal Psikoedukasi dan Konseling)
Abstract: This research and development aim to produce a product in the form of an achievement motivation training guidebook to improve academic efikasi diri for junior high school students in Karanganyar. This study uses a research and development design but is limited to expert validity testing. The subject of this product is 2 guidance and counseling experts. The data used to measure the level of product validity are expert test questionnaires and analyzed using the inter-rater agreement model. The results of the expert validity test analysis using the inter-rater model are in the very high category. for the LKPD book, the results of the validity test are 0.95 which belongs to the very high category. From these results, it is hoped that the next researcher can proceed to the next stage, namely the practicality test and the effectiveness test.